Perbandingan Reals Earning Management oportunistik dan sinyal terhadap kinerja operasional perusahaan publik: Reals Earnings Management (REM) - Choula Lutfia Ramadhani; Ahmad Fahruddin Alamsyah; Sri Andriani (CV. ITTC INDONESIA, 2025)
This study examines the impact of Real Earnings Management (REM) on the future operational services of UK public companies between 2009 and 2015. REM is conducted by actual business activities such as sales operations, discretionary spending adjustments, production changes, and others analyzed in relation to the battle of two profit networks: profit and previous year's profit. The results of the Fama-Macbeth regression model with Newey-West adjustment show that companies that deal with REM to meet profit thresholds tend to improve subsequent performance indicating an investor signaling function. In contrast, companies that use REM experience worsening without profit targets indicating opportunistic motivations. The results highlight the dual nature of REM-entweder, either as a strategic signaling mechanism or as a short-term opportunistic tool, and the importance of stakeholders to assess the intent behind earnings management practices.